Granulometric fractions of soil organic matter in intercropping of off-season corn with Marandu grass under nitrogen sources - Faccin, Fabiane Cargnin; Marchetti, Marlene Estevão; Serra, Ademar Pereira; Ensinas, Simone Cândido (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to determine the effect of off-season corn intercropped with Urochloa brizantha 'Marandu' and of nitrogen sources on the granulometric fractions of soil organic matter under a no-tillage system. The treatments were arranged in a 2x4 factorial arrangement – two types of corn cultivation (with or without pasture) and four nitrogen sources (without nitrogen, urea, ammonium sulfate+urea, and ammonium sulfate) –, in randomized complete blocks with four replicates. The experiment was carried out from 2005 to 2013. Soil sampling was performed in 2013, after corn harvest in fall/winter, at four depths: 0–5, 5–10, 10–20, and 20–40 cm. Total (TOC), labile (LC), particulate (POC), and mineral-associated organic carbon (MOC) contents were determined. The intercropping of corn with U. brizantha 'Marandu' results in a higher concentration of TOC, LC, and POC than single corn cultivated in fall/winter. Ammonium sulfate+urea increases TOC contents at the 0–5-cm depth, but decreases them at the 20–40-cm depth, besides increasing the MOC contents at all depths. The highest total, labile, and particulate organic carbon contents are observed at the 0–5 and 5–10-cm depths.